Micropropagation of Kluai Khai (Musa acuminata ‘Klaui Khai’) Using Sword Suckers and Inflorescences at Various Development Stages - Silayoi, Benchamas (Agriculture and Natural Resources, 2001)
Comparison the use of inflorescence at various stages of development versus meristem of sword suckers of Kluai Khai, as a source of the primary explants for in vitro culture was conducted . For shoot initiation, the explants were cultured on semi solid and liquid medium of Murashige and Skoog (1962) supplemented with 5 ppm. of 6-benzylaminopurine (BA). It was found that on liquid medium, the culture produced the first shoot faster than the ones on semi solid medium. The first shoot of suckers occurred on the 30th and 45th days after culturing on liquid medium, and semi solid medium respectively, while those at the 5th, 3th and 1st days of developmental stage occurred on the 52nd, 52nd and 56th days of culturing respectively. After 2 months, the sucker on liquid medium was noticed to give the shoot number of 1.88 shoots per explant, where as on semi solid medium, it yielded 0.6 shoot per explant. The shoot number of inflorescence at the 5th, 3rd and 1st days of developmental stage cultured on liquid medium were 2.08 (the highest), 1.93 and 1 shoots per explant respectively. At this stage, no development of the shoots on semisolid medium had been found to develop yet. Shoot multiplication was also revealed to be stimulated by transferring explants into semi solid medium, thus yielding such higher shoot number than the others. On the 5th month, the inflorescence at the 5th day of developmental stage gave the highest shoot number of 9.06 shoots per explant which was not significantly different from those of 8.9 shoots per explant at the 3rd day of developmental stage. The shoot number of the others were significantly lower different. 10% off-type shoots, occurred in inflorescence culture. After transplanting plantlets to the nursery, the survival rate was 96 percent.